Cross-sectional study of the association between diet and physical inactivity with obesity, diabetes and hypertension among older adults in Sierra Leone - Justine Davies; Oyinlola Oyebode; Haja Wurie; Maria Lisa Odland; Miles Witham; Rashid Ansumana; Tahir Bockarie; Joseph Lamin; Ankit Shanker; Mohamed B Jalloh; Alhaji M Kamara (BMJ Open)
Objective To examine the association between behavioural risk factors and their physiological sequelae among adults aged 40 and above in Bo District, Sierra Leone.Design Cross-sectional study.Setting Household survey in Bo District, Sierra Leone.Participants The study included 1978 randomly sampled adults aged 40 and above (44.4% male and 55.6% female). The majority of participants were aged 40–49 years (34.5%). Data were collected using a household survey based on the validated WHO STEPs questionnaire.Methods Multivariable logistic regression analysis was performed to determine associations between behavioural risk factors (diet, physical activity and salt intake) and the presence of hypertension, diabetes and/or obesity, adjusting for sociodemographic variables.Primary outcome measure The primary outcomes were the presence of hypertension, diabetes or overweight/obesity. Hypertension was defined as systolic blood pressure of ≥140 mm Hg and/or diastolic blood pressure of ≥90 (measured); diabetes as fasting glucose of ≥7.0 mmol/L, random plasma glucose level of ≥11.1 mmol/L or the use of antidiabetic medications (self-reported) and overweight/obesity as having a body mass index of ≥25 kg/m² (measured).Results At least one physiological risk factor for cardiovascular diseases, that is, hypertension, obesity or diabetes, was present in 43.5% of participants. Hypertension was associated with urban living (OR=1.46, 95% CI (1.41 to 1.51)), older age (OR for 80+=3.98, 95% CI (3.70 to 4.28)), insufficient fruit and vegetable intake (OR=1.52, 95% CI (1.46 to 1.60)) and low physical activity (OR=1.35, 95% CI (1.27 to 1.43)). Diabetes was associated with urban residence (OR=1.84, 95% CI (1.66 to 2.05)), older age (OR for 70–79=3.82, 95% CI (3.28 to 4.45)), low fruit and vegetable consumption (OR=1.61, 95% CI (1.36 to 1.90)), high salt intake (OR=1.34, 95% CI (1.21 to 1.49)) and low physical activity (OR=1.47, 95% CI (1.26 to 1.71)). Obesity was associated with urban living (OR=1.66, 95% CI (1.59 to 1.72)), high salt intake from two or more sources (OR=1.21, 95% CI (1.17 to 1.25)) and low physical activity (OR=1.30, 95% CI (1.22 to 1.39)). Male sex (OR=0.37, 95% CI (0.36 to 0.38)) and older age (OR for 80+=0.39, 95% CI (0.35 to 0.43)) were protective factors.Conclusions In Bo District, nearly half of adults over 40 face hypertension, diabetes or obesity, especially urban dwellers, older age groups and those eating too few fruits and vegetables, consuming excess salt and getting little exercise. Public health efforts should focus on urban‐targeted nutrition education, salt‐reduction strategies, community exercise programmes and routine blood pressure and glucose screening, working with local leaders to ensure sustainable lifestyle changes and early disease detection.